ETHNOMATHEMATICS OF JAVANESE CULTURE IN THE INQUIRY LEARNING MODEL - Pardimin Pardimin; Didi Supriadi (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
The research aims to develop an inquiry learning model based on Javanese cultural ethnomathematics. This research uses research and development methods with the Plomp educational development model. Research stages include:1) preliminary research, 2) development or prototyping phase, and 3) assessment phase. In this research, the development stage was carried out at the initial investigation stage and the design stage which included field observations, literature studies, focus group discussion, preparation of learning models and learning tools and continued with small-scale trials. Field observations were carried out through observing cultural sites and junior high schools at three provinces in Indonesia, Yogyakarta province, West Java province, and East Java province. Data collection techniques in this research are interviews, observation and questionnaires. The data obtained was analyzed using quantitative descriptive analysis techniques. The development results at the initial investigation stage generated a preliminary syntax for the inquiry learning model. The subsequent design stage produced a complete mathematics learning model based on Javanese cultural ethnomathematics, documented in a comprehensive book accompanied by learning tools. Trial results indicated that the developed inquiry learning model meets valid criteria and is suitable for classroom implementation. The significance of this research lies in its contribution to integrating local cultural knowledge into mathematics instruction through an inquiry-based pedagogical approach. By embedding Javanese ethnomathematical concepts into structured inquiry learning, this study provides an innovative model that supports contextualized learning and aligns with national curriculum demands for culturally relevant pedagogy. Furthermore, the model offers a practical framework for teachers to develop meaningful learning experiences that bridge formal mathematics with students’ cultural environments.